THE SOCIOLINGUISTIC AND CULTURAL DIMENSIONS OF TABOO WORDS IN AUSTRALIAN ENGLISH: A STUDY ON AUSTRALIAN TOURISTS IN BALI - Gede Krisna Widiantara; I Gede Budasi; Gede Mahendrayana (Yayasan Literasi Sains Indonesia, 2025)
The phenomenon of using swear words in Australian English is worth studying because it not only serves as an expression of emotion but also reflects the social and cultural values of its speakers. In cross-cultural interactions, such as Australian tourists visiting Bali, the use of such words has the potential to cause misunderstandings. This study aims to identify and explain the forms, functions, and references of swear words in Australian English from a sociolinguistic and cultural perspective. The research employed a descriptive qualitative method with a sociolinguistic approach. Primary data were collected through in-depth interviews with Australian tourists, while secondary data were obtained through document analysis. Three informants were selected based on specific criteria, with the researcher serving as the main instrument, supported by field notes, questionnaires, and interview guidelines. The findings revealed 32 Australian English swear words categorized by their forms, consisting of words (11), phrases (13), and clauses (8). In terms of function, these swear words were used to draw attention, discredit, provoke, establish interpersonal identification, express emotions, provide emphasis, and show aggression. Based on their references, the swear words were related to sexuality (16), excrement (7), religion (4), and personal background (3). The study concludes that the use of swear words in Australian English is not only a means of emotional communication but also an integral part of the speakers’ cultural identity